2004
DOI: 10.1128/jcm.42.11.5139-5145.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia kruczakiae sp. nov., a Pathogen in Immunocompromised Patients and a Member of the “ N. nova Complex”

Abstract: Molecular methodologies have become useful techniques for the identification of pathogenic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…The 99.3% similarity of the 16S rRNA genes of isolates 7, 8, and 9 to the 16S rRNA gene sequence of the type strain of N. blacklockiae is also less than the 16S rRNA gene sequence similarity of some distinct species to each other. For example, the species N. kruczakiae and N. veterana and the species N. paucivorans and N. brevicatena show 99.8 and 99.5% similarity to each other, respectively (5,25). The results of a BLAST (Basic Local Alignment Search Tool; NCBI, Bethesda, MD) analysis of the 16S rRNA gene sequences of isolates 7, 8, and 9 indicate that the next most similar type strains to these isolates are those of N. transvalensis and N. wallacei, with 98.6 and Յ98.4% similarities, respectively, which are significantly less than the similarities of these isolates to the N. blacklockiae type strain.…”
Section: Discussionmentioning
confidence: 99%
“…The 99.3% similarity of the 16S rRNA genes of isolates 7, 8, and 9 to the 16S rRNA gene sequence of the type strain of N. blacklockiae is also less than the 16S rRNA gene sequence similarity of some distinct species to each other. For example, the species N. kruczakiae and N. veterana and the species N. paucivorans and N. brevicatena show 99.8 and 99.5% similarity to each other, respectively (5,25). The results of a BLAST (Basic Local Alignment Search Tool; NCBI, Bethesda, MD) analysis of the 16S rRNA gene sequences of isolates 7, 8, and 9 indicate that the next most similar type strains to these isolates are those of N. transvalensis and N. wallacei, with 98.6 and Յ98.4% similarities, respectively, which are significantly less than the similarities of these isolates to the N. blacklockiae type strain.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 16S rRNA gene sequencing is considered a better method for identification of Nocardia to the species level (Borriello et al, 2007), although certain isolates that have been found to have a high sequence similarity (99.8 %) from 16S rRNA sequences are recorded as distinct species by DNA-DNA hybridization (Conville et al, 2004;Rodríguez-Nava et al, 2006). McTaggart et al (2010) applied multilocus sequence analysis to 190 clinical isolates of Nocardia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, taxonomy of this genus has undergone considerable changes due to modern molecular techniques, such as identification by 16S ribosomal RNA gene sequencing. New species have been described, such as N. cryacigeorgica (Schlaberg et al, 2008), N. veterana (Pottumarthy et al, 2003), N. abscessus (Yassin et al, 2000), N. paucivorans (Eisenblatter et al, 2002) and N. kruczakiae (Conville et al, 2004), which should be taken into account in case of isolation in LTx samples.…”
Section: General Aspectsmentioning
confidence: 99%